Ethics committees of journalists: acting, visibility and effectiveness - Christofoletti, Rogério (2015)
Journalists have some monitoring tools and ethical oversight, and the best known are the codes of ethics. Ethics committees, linked to unions, have the responsibility to ensure compliance with the ethics rules. This article evaluates these commissions in 31 unions affiliated to the National Federation of Journalists (Fenaj), considering the frequency of its operations, visibility in the category and its operating conditions. For that, we turn to analysis of the websites of the trade unions and the questionnaires answered by members of ethics committees. The results identify little public visibility of commissions, cultural and structural difficulties, and a timid performance within the category.